2009
DOI: 10.1590/s1519-69842009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics: seasonal variation of phytoplankton functional groups in brazilian reservoirs (Billings and Guarapiranga, São Paulo)

Abstract: Phytoplankton may function as a "sensor" of changes in aquatic environment and responds rapidly to such changes. In freshwaters, coexistence of species that have similar ecological requirements and show the same environmental requirements frequently occurs; such species groups are named functional groups. The use of phytoplankton functional groups to evaluate these changes has proven to be very useful and effective. Thus, the aim of this study was to evaluate the occurrence of functional groups of phytoplankto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
(34 reference statements)
5
19
1
7
Order By: Relevance
“…The temporal shifts in the abundance of such groups reflected the characteristics of the environment. The high percentages of Cylindrospermopsis raciborskii in the winter (27 and 36% at SS2 and SS3, respectively) were compatible with the lower TN concentrations in this period, a tolerance typical of the Codon S N , as verified in 2 other Brazilian reservoirs (Gemelgo et al 2009). Cryptomonas erosa (Y), Botryococcus braunii (F), and Kirchneriella obesa (F) constituted 44% of the phytoplankton community at the SS4 site in spring, probably owing to their tolerance of low water column transparency (TSS = 48.1 mg/L).…”
Section: Resultssupporting
confidence: 67%
“…The temporal shifts in the abundance of such groups reflected the characteristics of the environment. The high percentages of Cylindrospermopsis raciborskii in the winter (27 and 36% at SS2 and SS3, respectively) were compatible with the lower TN concentrations in this period, a tolerance typical of the Codon S N , as verified in 2 other Brazilian reservoirs (Gemelgo et al 2009). Cryptomonas erosa (Y), Botryococcus braunii (F), and Kirchneriella obesa (F) constituted 44% of the phytoplankton community at the SS4 site in spring, probably owing to their tolerance of low water column transparency (TSS = 48.1 mg/L).…”
Section: Resultssupporting
confidence: 67%
“…, Margalef 1983) show eutrophication of the ecosystem (Tundisi et al 2008, Gemelgo et al 2009, Silva et al 2011, due to the high degree of decomposition of organic matter, which releases greater amount of ions in the water column (Matsukazi et al 2004), commonly observed in reservoirs of northeast of Brazil (Chellapa et al 2008b, Costa et al 2009). In the present work, there were greater conductivity values in the rainy season, a result supported by Oliveira et al (2011) andLira et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, esse tipo de abordagem é menos comum para reservatórios de usos múltiplos. Gemelgo et al (2009) examinaram a variação sazonal dos grupos fi toplanctônicos nos reservatórios Billings e Guarapiranga (SP), cuja água é utilizada para abastecimento público, industrial e recreação. A principal conclusão nesse caso foi que a dinâmica temporal do fi toplâncton esteve associada à temperatura, extensão da zona eufótica, turbidez, condutividade, pH e concentrações de oxigênio dissolvido, nitrato e fósforo total.…”
Section: Introductionunclassified